MODEL PEMBERDAYAAN PETANI SALAK MENJADI “PENELITI” DAN “PENYULUH SWADAYA” - Samsi Hariadi, Sunarru (PIRAMIDA; Vol 3, No.2 Desember 2007)
Decreasing in genetic variability of salak/Salacca zalacca (Gaertner) in Sleman Regency D.I. Yogyakarta Province will give disadvantage impact, because it will drive on explosion of pest and disease. To solve this problems, Faculty of Agriculture Gadjah Mada University conducted training about “Germ Plasm Conservation and Biological Control” for salak farmers. Training was conducted by action research method, farmers participated was guidanced to become researcher and volunteer extension worker. One year after training, farmers participated was evaluated in the field. Result of the evaluation show that many farmers participated have conducted “trial and error” for research, have given agricultural extension to other salak farmers. So, there were diffusion of agricultural innovation in villages.
Keywords: genetic variability, training, researcher, volunteer extension worker